Diamagnetic to Ferromagnetic Like Transition of Non-Stoichiometry Barium Titanate (BaTiO3-x) Prepared by Sol-gel Method - Soegijono, Bambang; Susetyo, Ferry Budhi; Notonegoro, Hamdan Akbar; Raksa, Teguh Yoga (Science and Technology Indonesia, 2024)
The oxygen vacancy properties are significant, creating ferromagnetic properties of material in metal oxide systems like dilute magnetic semiconductors. An aqueous sol-gel method has been used in the present study to synthesize non-stoichiometry BaTiO3-x polycrystalline. In an attempt of examining the oxygen deficiency consequences on the magnetic properties, the gel samples were sintered (1000◦C) at various times (6, 12, 18, and 24 hours) under a vacuum environment. This study employs an X-ray diffraction apparatus in terms of characterizing segments and structures of the samples. It also investigates morphology and element distribution on the surface of the samples exploiting an Electron microscope where Energy dispersive spectroscopy is supplied. For the purpose of characterizing the magnetic properties of the samples, it applies vibrating sample magnetometers. The chemical state of the element and its corresponding bond to other elements was identified using X-ray photoelectron spectroscopy. Single-phase compounds were observed. The crystal system is tetragonal, but the crystal parameters are different. Increase sintering time leads to increase crystallite size and decrease in micro strain. Moreover, sintering in a vacuum environment results in oxygen deficiency and leads to the atomic ratio of Ba/Ti change as the sintering time increases. The Ba/Ti ratio change affects the transformation from diamagnetic to ferromagnetic-like. The elements (Ba, Ti and O) chemical state is shown and its bonding to the corresponding element along with the X-ray photoelectron spectroscopy pattern of the BTX2 sample. The element of oxygen binds to Ti and Ba while Ba element exists in two chemical states.